2019
DOI: 10.3390/tropicalmed5010002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Community-Based Systematic Screening of Household Contacts of Patients with Multidrug-Resistant Tuberculosis in Myanmar

Abstract: Screening of household contacts of patients with multidrug-resistant tuberculosis (MDR-TB) is a crucial active TB case-finding intervention. Before 2016, this intervention had not been implemented in Myanmar, a country with a high MDR-TB burden. In 2016, a community-based screening of household contacts of MDR-TB patients using a systematic TB-screening algorithm (symptom screening and chest radiography followed by sputum smear microscopy and Xpert-MTB/RIF assays) was implemented in 33 townships in Myanmar. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A study from Myanmar among household contacts of index patients with RR-TB reported a yield of 10.0% for children aged <5 years. 22 Fox et al. found a similar yield of 10.0% among TB contacts aged <5 years, and Honjepari et al.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A study from Myanmar among household contacts of index patients with RR-TB reported a yield of 10.0% for children aged <5 years. 22 Fox et al. found a similar yield of 10.0% among TB contacts aged <5 years, and Honjepari et al.…”
Section: Discussionmentioning
confidence: 84%
“…Our overall yield was 0.7%, which is lower than those in the studies we reviewed, which had an average overall yield of 2.50 (range 0.96–6.50). 7 , 18 20 , 22 27 DR-TB studies reported overall yields of 3.1%, 3.9% and 6.5%, 20 , 22 , 23 and yields of 1.4% and 3.4% were reported in DR-TB subgroups within larger TB cohorts. 19 , 25 The NNS is the reciprocal of the overall yield.…”
Section: Discussionmentioning
confidence: 96%
“…Kyaw et al reported a yield of active TB of 3.9% among HHCs of MDR-TB index patients, with the highest yield of 10% among children under 5 years old. However, only a minority of TB patients diagnosed had rifampicin resistant (RR) TB [ 12 , 13 ]. Finally, Paryani et al reported an incidence rate of TB of 2072/100,000 person years in the HHCs of index patients with pre-extensively drug resistant (pre-XDR) and XDR-TB following initial screening, which shows the importance of ongoing follow up and preventive treatment among HHCs [ 14 ].…”
mentioning
confidence: 99%